The Syntax Analysis in Relative Clause Found in the Novel “The Wonderful Wizard of OZ” (e-Journal of Linguistics, 2023)
The paper analyses syntax analysis in relative clause found in the novel“The Wonderful Wizard of Oz”. “The Wonderful Wizard of Oz” is aliterary work of kid story by Lyman Frank Baum and the illustrationwas made by W.W. Denslow. Dorothy lived with her Aunt Em, UncleHenry and her dog, Toto. Theory of relative clauses that was proposedby Quirk (1985), Sneddon (1996) and was supported by other theories.The theory used to analyze the syntax structure was the theory proposedby Brown and Miller. The method that was used to get the data wasqualitative, library research. The data were taken from the novelentitled “The Wonderful Wizard of Oz”. This research study aims to: (i)analyze the syntax structure in the relative clause found in the novelentitled “The Wonderful Wizard of Oz”, (ii) analyze the types ofrelative clauses in the relative clauses found in the novel entitled “TheWonderful Wizard of Oz”.
Keywords: Relative clause; syntax analysis; linguistics